Trends in incidence of primary brain cancer in New Zealand, 1995 to 2010 - Stella J‐H Kim; Sally J. Ioannides; J. Mark Elwood (Elsevier, 2015)
Abstract Objective: Case‐control studies have linked mobile phone use to an increased risk of glioma in the most exposed brain areas, the temporal and parietal lobes, although inconsistently. We examined time trends in the incidence rates of brain malignancies in New Zealand from 1995 to 2010. Methods: Data from the New Zealand Cancer Registry was used to calculate incidence rates of primary brain cancer, by age, gender, morphology and anatomical site. Log‐linear regression analysis was used to assess trends in the annual incidence of primary brain cancer; annual percentage changes and their 95% confidence intervals were estimated. Results: No consistent increases in all primary brain cancer, glioma, or temporal or parietal lobe glioma were seen. At ages 10-69, the incidence of all brain cancers declined significantly. Incidence of glioma increased at ages over 70. Conclusion: In New Zealand, there has been no consistent increase in incidence rates of primary brain cancers. An increase in glioma at ages over 70 is likely to be due to improvements in diagnosis. As with any such studies, a small effect, or one with a latent period of more than 10 to 15 years, cannot be excluded.